2020
DOI: 10.1101/2020.10.14.20212340
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early Prediction of COVID-19 Severity Using Extracellular Vesicles and Extracellular RNAs

Abstract: The clinical manifestations of COVID-19 vary broadly, ranging from asymptomatic infection to acute respiratory failure and death. But the predictive biomarkers for characterizing the variability are still lacking. Since emerging evidence indicates that extracellular vesicles (EVs) and extracellular RNAs (exRNAs) are functionally involved in a number of pathological processes, we hypothesize that these extracellular components may be key determinants and/or predictors of COVID-19 severity. To test our hypothesi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…They found that fibrinogen gamma chain (FGG), CD147, calpain 2 (CAPN2), extracellular matrix protein 1 (ECM1), coat complex subunit beta 2 (COPB2), KRAS proto-oncogene (KRAS), protein kinase C beta (PRKCB) and ras homolog family member C (RhoC) were significantly more abundant in SARS-COV-2 infected patients than in healthy donors. This group of markers can distinguish between severe and mild cases of COVID-19; among them, COPB2 has the best predictive value [ 147 ].…”
Section: Covid-19-associated Thrombosis and Extracellular Vesiclesmentioning
confidence: 99%
“…They found that fibrinogen gamma chain (FGG), CD147, calpain 2 (CAPN2), extracellular matrix protein 1 (ECM1), coat complex subunit beta 2 (COPB2), KRAS proto-oncogene (KRAS), protein kinase C beta (PRKCB) and ras homolog family member C (RhoC) were significantly more abundant in SARS-COV-2 infected patients than in healthy donors. This group of markers can distinguish between severe and mild cases of COVID-19; among them, COPB2 has the best predictive value [ 147 ].…”
Section: Covid-19-associated Thrombosis and Extracellular Vesiclesmentioning
confidence: 99%
“…EVs are lipid bilayer membrane-bound structures, which are released from various kinds of cells, and contain many bioactive compounds (cargo) such as mRNAs, microRNAs (miRNAs), DNA, lipids, and various proteins. Due to their intact structure, EVs can circulate through body fluids freely and can deliver their cargo to neighboring or remote cells to help maintain their physiological condition [12].…”
Section: Covid-19-associated Multiple Organ Failure and Ev-mediated Recoverymentioning
confidence: 99%
“…All aspects of exosomes on treatment of COVID-19 or its related symptoms is discuses on reference: (Kadriyan et al, 2020,). EVs interestingly not only can be useful for treatment but also could predict the severity of COVID-19 (Fujita et al, 2020;Inal, 2020;Rosell et al, 2020). Khatri et al studied the effect of MSC-EVs on lung epithelial cells.…”
Section: Uc-mscmentioning
confidence: 99%